Seismic performance analysis of tower crane mast types with different bracing configurations - Kenan, Hamit; Azeloglu, Oktay (ELSEVIER SCIENCE INC, 2021)
Tower cranes, which are composed of a lattice structure, are mostly used to transport heavy materials and equipment in construction sites. The delicate structure of tower cranes and operating conditions make them very sensitive to dynamic excitation such as instant overload for any reason caused by transported material or wind and earthquake effect. This study was carried out for investigating the seismic performance of tower crane mast types with different kinds of bracing configurations. A program with respect to finite element method was written in MATLAB which is capable of meshing, modal analysis, and transient analysis. While nodal coordinates, material information, cross-section data, and the orientation of cross-section for each element in the structure and earthquake motion in the time domain are used for input data in the program, natural frequencies, mode shapes, mass participation factors of the structure and displacement, velocity and acceleration response of each node are obtained as output parameters. In this research, different types of mast frames were designed in terms of the most commonly used bracing configuration and were used in modal and transient analysis using two different earthquake motion inputs. The seismic performance of each mast type was determined in the time domain in terms of dynamic response characteristics.
Keywords: Tower crane; Bracing; Seismic performance; Modal analysis; Transient analysis; Finite element model; DYNAMIC-RESPONSE; CONTAINER CRANES; BRACED FRAME; COLUMNS; Engineering